A comparison of urban and non-urban African American older adults on health-related characteristics. (21st October 2018) - Oh, Hyejung; Noh, Hyunjin; Sims, Omar T.; Guo, Yuqi; Sawyer, Patricia
ABSTRACT: Although residential geographic health disparities have been noted in the previous literature, studies are specifically lacking on intra-group health comparisons of African American older adults by residential geography. The purpose of this study was to determine if health-related characteristics of African American older adults varied by residential geography. Socioeconomic demographics, medical conditions, primary care use, and self-ratings of general health, social activity, and physical activity were compared in a community-dwelling sample of 327 urban and non-urban African American older adults. Urban and non-urban African American older adults were compared on health-related factors. Compared to urban African American older adults, those in non-urban areas had lower incomes, lower self-ratings of general health, social activity, and physical activity, and a higher frequency of arthritis and gastroenterological and urological conditions. Despite poorer general health and medical conditions, non-urban African American older adults were less likely to visit the doctor when needed. Study findings suggest residential geography may be an underappreciated underlying contributing factor to inter-group health disparities between African American and white older adults and not race alone. Therefore, social workers in public health, health care, and clinical settings should be aware of the interaction between race and residential geography.